2020
DOI: 10.1172/jci126923
|View full text |Cite
|
Sign up to set email alerts
|

Arginase impedes the resolution of colitis by altering the microbiome and metabolome

Abstract: Arginase 1 (Arg1), which converts l-arginine into ornithine and urea, exerts pleiotropic immunoregulatory effects. However, the function of Arg1 in inflammatory bowel disease (IBD) remains poorly characterized. Here, we found that Arg1 expression correlated with the degree of inflammation in intestinal tissues from IBD patients. In mice, Arg1 was upregulated in an IL-4/ IL-13and intestinal microbiota-dependent manner. Tie2-Cre Arg1 fl/fl mice lacking Arg1 in hematopoietic and endothelial cells recovered faster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 92 publications
3
60
0
Order By: Relevance
“…S4 ). Additionally, arginase activity, shown to be the opponent of inducible nitric oxide synthase (iNOS) but also in recent years discussed to be critical in the development of inflammatory bowel diseases [ 39 , 40 ], was significantly lower in proximal small intestine of FFC-fed mice when compared to FFC + L-Cit-fed animals ( Fig. 4 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…S4 ). Additionally, arginase activity, shown to be the opponent of inducible nitric oxide synthase (iNOS) but also in recent years discussed to be critical in the development of inflammatory bowel diseases [ 39 , 40 ], was significantly lower in proximal small intestine of FFC-fed mice when compared to FFC + L-Cit-fed animals ( Fig. 4 ).…”
Section: Resultsmentioning
confidence: 96%
“…Arginase has been shown before to be the counter regulator of nitric oxide synthases, including also iNOS, thereby also regulating the bioavailability of NO [ 61 ]. Also, in recent years, results obtained in humans with inflammatory bowel disease and of rodent models of inflammatory bowel diseases suggest that alterations of intestinal arginase and herein especially arginase 1 found in macrophages and endothelial cells [ 62 ], may be critical in the development of inflammatory alterations in these diseases [ 40 , 63 ]. In the present study, contrasting these findings of others, protein levels of arginase 1 were below the level of detection.…”
Section: Discussionmentioning
confidence: 99%
“…The communication is most likely bidirectional, whereby SCFAs affect not only immune processes but also, immune cells and their mediators regulate the gut microbiota. For example, it has recently been reported that arginase can alter the microbiome 50 . In addition, the gut microbiome can be considered a hub for integrating signals from the immune and other body systems 51 .…”
Section: Discussionmentioning
confidence: 99%
“…As an illustration of the importance of such metabolism, the levels of AHR ligands produced by the gut microbiota have been recently shown to be reduced in patients with celiac disease (Lamas et al, 2020). Conversely, the activity of host amino-acid catabolizing enzymes can influence the availability of amino acids to the microbiota, with consequences on local inflammation, as shown by the role of host Arg1 on the composition of microbiota and bacterial production of protective polyamines in a mouse model of inflammatory bowel disease (Baier et al, 2020). Thus, the microbiota participates in local immune homeostasis through its amino-acid catabolizing activity and alterations of such activity can lead to immunopathology.…”
Section: Bacterial-host Interactions In the Production Of Amino-acid mentioning
confidence: 99%